How Has The Globalization of Labor Affected the Labor Income Share in Advanced Countries? - Jaumotte, Florence (IMF Working Papers; Working Paper ;, 2007)
Labor markets around the world have become increasingly integrated over the last two decades, with the entry of China, India and the former Eastern bloc into the world trading system, the removal of restrictions on trade and capital flows, and rapid technological progress. At the same time, the share of labor in national income decreased in most advanced countries. This paper uses a labor share equation derived from a translog revenue function to estimate the contributions of globalization, technological progress, and labor market policies to the decline in the labor share. The results, obtained for 18 advanced countries over 1982- 2002, suggest that globalization was only one of several factors that have affected the labor share. Technological progress, especially in the information and communications sectors, has had a bigger impact, particularly on the labor share in unskilled sectors.